English Teachers Storytelling Strategy in Teaching Speaking Class at Junior High School 17 Barru - Sri Putri Ramadhani; Haryanto Atmowardoyo; Sultan Baa (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The objectives of the research were to find out (1) the teacher classroom implementation of storytelling strategy in speaking class in Junior High 17 Barru; and (2) the student’s perception on the impact of storytelling strategy to their speaking achievement in Junior High 17 Barru. This research applied qualitative method. The participants of the study were two English teachers and five students from Junior High School 17 Barru. The subjects were chosen by using purposive sampling technique. The data collected were observation checklist and interview. The results of this study showed that (1) the teacher classroom implementation of the storytelling strategy in teaching the speaking class, teacher A choose discussion group as strategy in class and teacher B provides individual attention and based on the strategies used  had the potential to improve vocabulary to the students and helped the students to build confident in speaking (2) the students perceptions on the impact of the storytelling strategy on their speaking achievement are that it helps build their confidence in speaking by telling stories in front of the class and enables them to expand their vocabulary by creating their own stories.Key words--  Blindfold,  Junior  high  school,  and  Vocabulary  mastery